Сравнительный анализ двух подходов к исследованию параметрических колебаний ортотропных пластин сложной формы - Мазур, Ольга Сергеевна (НТУ "ХПИ", 2013)
Parametric vibrations of the orthotropic plates with complex form and various boundary conditions are studied by two approaches. The first method uses the movement equations in terms of displacements; the second approach is based on using the equations in mixed form. The results obtained by the presented algorithms are compared for T-plate.
Keywords: устойчивость динамическая; теория R-функций; условия граничные; уравнения движения; пластина Т-образная